The importance of market signals in crop varietal development: Lessons from Komboka rice variety - Ng'endo, Mary; Kinyua, MaryLiza; Chebet, Lourine; Mutiga, Samuel K.; Ndung’u, Joseph; Nyongesa, Oliver; Njau, Simon; Panchbhai, Ajay; Musila, Ruth; Murori, Rosemary (Springer, 2022)
Growing high-yielding varieties is crucial for successful crop production and maximizing farmers’ net returns. One such example is IR05N221, locally referred to as Komboka rice variety, which was released in Kenya in 2013. On the one hand, Komboka can bridge the gap in rice imports since yields of existing rice varieties do not meet the increasing rice consumption levels of the Kenyan population. On the other hand, it has taken about seven years for Komboka to be appreciated by farmers, necessitating the need to understand farmer preferences when it comes to adopting a new improved variety. We used a mixed-method study approach by combining quantitative and qualitative data collected regionally and locally in both rainfed and irrigated ecologies. When compared to most of the other rice varieties under evaluation, Komboka was high-yielding, early-maturing, and had moderate tolerance to diseases in both rainfed and irrigated ecologies. However, farmers at the regional level ranked Komboka either at the same or lower rank in terms of sensory attributes. At the local level, farmers predominantly grew older and more aromatic Basmati 370 rice variety for sale, as it fetched them more money, with preferences for both men and women rice farmers being the same. Despite Komboka being a high-yielding variety, Mwea rice farmers’ perceptions and preferences for this improved variety were low. While Komboka was equally aromatic, the lack of a ready market dissuaded these farmers from widely preferring the new Komboka variety. We provide prerequisite information that can support the commercialization and promotion of the Komboka variety. We also show that widespread favourable perception of new varieties hinges on matching preferences between breeders’ efforts for improved rice productivity with farmers’ needs for market competitiveness in these new varieties.